Analysis on the AIDCA Method in Website UX Design Copywriting - Fatkhur Rochman; Abdul Waris S.; Eko Boedhi Santoso; Izzatul Ulya (International Journal of Social Science and Community Service, 2024)
This study aims to evaluate the quality of copywriting on the Papillon's Sisters website using the Heuristic Evaluation method which focuses on the AIDCA model (Attention, Interest, Desire, Conviction, Action). The evaluation is conducted through direct observation of the main pages of the site, using an AIDCA-based checklist to measure the effectiveness of copywriting in attracting attention, maintaining interest, arousing desire, building conviction, and encouraging user action. The data collected was analysed qualitatively by giving a severity rating to each problem found, ranging from Good Practice to Major Issue. The results showed that copywriting on the website has some strengths in terms of consistency of writing and attractive visuals, but there are deficiencies in the emotional aspects of language, lack of detailed product descriptions, and ineffective calls-to-action. From the evaluation, 5 major issues, 4 normal issues, 2 minor issues, and 1 good practice were found. This research provides recommendations for improvement, such as the use of more emotional language and improved visual layout to increase user engagement and conversion on the Papillon's Sisters website.